Voz do professor: relação entre avaliação perceptivo - auditiva, autorreferência a sintomas e índice de desvantagem vocal - Mestre, Lhaís Renata (2012)
Teachers lack of knowledge about voice disorders is frequently pointed out in Speech-Language Pathology literature. Teachers do not identify vocal issues and seek assistance only when the disorder is extremely pronounced. Aim: To relate the presence of voice disorder (auditory perceptual analysis), self-reported vocal symptoms and laryngeal sensations and the voice handicap index in teachers. Method: This study was conducted with 40 teachers (elementary, middle and high school) of a private school located in a city of the state of São Paulo. The subjects answered the Teacher Vocal Production Conditions (CPV-P) questionnaire (in order to assess social-demographic aspects, voice symptoms and laryngeal sensations) as well as the Voice Handicap Index (VHI) (to know the impact of voice disorder in the lives of the teachers). After questionnaire completion, speech samples were collected from each of the 40 teachers in order for Speech-Language Pathology assessment. Each teacher was asked to say a sustained vowel /a/ and /i/, and the months of the year. A sample of spontaneous speech (regarding a retelling of their weekend and a class simulation) was also recorded. This procedure took 15 to 20 minutes. The material was edited and 20% of speech samples were added to the original 40 voice samples (total 48 recordings) so that three Speech-Language Pathologist judges could analyze the material. The judges were specialized in voice pathology, had a minimum of five years experience and did not know the studied population. The evaluation performed by the judge with the greatest internal consistency was used to compose two groups: with and without voice disorder. After a descriptive statistical analysis, voice disorder was associated to the variables age, sex, marital state, schooling, type of employment, years of teaching and number of hours worked per week, as well as to voice symptoms and laryngeal sensations (CPV-P), total VHI score and score of each domain and question. The chi-square test was used for this purpose, with level of significance lower than 0.05%. Results: In the comparison between the groups there was no statistically significant difference regarding the social demographic variables. Self-reported hoarseness differentiated the groups (p=0,011) as well as laryngeal sensations such as strained speech (p< 0,001) and sore throat (p<0, 001). All of the domains in the VHI as well as its total score differentiated the groups (p<0, 001). When the questions of each domain of the VHI were analyzed, 13 of the 30 questions differentiated the groups, mostly those pertaining to the organic domain. Conclusion: There was a statistically significant difference between the presence of voice disorder and voice symptom hoarseness, and the laryngeal sensations of strained speech and sore throat, as well as the general score, functional, organic and emotional domains of the Voice Handicap Index